Hubungan Dukungan Keluarga Dengan Mekanisme Koping Pasien Diabetes Mellitus - Tri - Juliansyah; Veny - Elita; Bayhakky - - (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2014)
The purpose of  this research is to determine the relationship between family’s support and coping mechanisms of diabetes mellitus patients at Arifin Achmad Hospital. Methodology on this research is a descriptive correlative with cross sectional approach. The number of sample is 30 respondents who is take by convenience sampling (accidental sampling) technique. The measurement tool of this research is questionnaire which consist of 18 questionnaire of family’s support  and 19 questionnaire of coping mechanims.This research use Chi-Square test as bivariate analysis. The results of this research shows 11 respondents (36,7%) have high level of family’s support and have adaptive coping mechanisms and 6 respondents (20% ) with maladaptive coping mechanisms. The results also show 3 respondents (10%) have low level of family’s support with adaptive coping mechanisms,and 10 respondents (33,3%) have maladaptive coping mechanisms. The results of Chi-Square test get p value 0,058 > 0,05, it means that there is no relationship between family’s support and coping mechanisms of patient with diabetes mellitus in Arifin Achmad Hospital Pekanbaru. It is suggested to health care provider to pay attention to patients health’s condition not only in physical aspect but also in pyschology. Keywords : Coping mechanisms, diabetes mellitus, family’s support